Dawwang kababaihang tagapagtanggol ng Kordilyera - Martinez, Nina; Gantala Press ([Makati, Philippines] Gantala Press, 2021)
On indigenous women movement against the dam projects in Cordillera Administrative Region, Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: Indigenous peoples -- Philippines -- Cordillera Administrative Region -- Comic books, strips, etc; Social movements -- Philippines -- Cordillera Administrative Region -- Comic books, strips, etc; Women revolutionaries -- Philippines -- Cordillera Administrative Region -- Comic books, strips, etc